Facile Synthesis of Functional Mesoporous Organosilica Nanospheres and Adsorption Properties Towards Pb(II) Ions - Liping Deng; Shichun Gu; Ruyi Wang; Yapeng He; Hairong Dong; Xue Wang (Nanomaterials)
We successfully synthesize monodisperse sulfhydryl-modified mesoporous organosilica nanospheres (MONs-SH) via one-step hydrolytic condensation, where cetyltrimethylammonium chloride and dodecyl sulfobetaine are employed as dual-template agents with (3-mercaptopropyl)triethoxysilane and 1,2-bis(triethoxysilyl)ethane as the precursors and concentrated ammonia as the alkaline catalyst. The prepared MONs-SHs deliver a large specific surface area (729.15 m2 g−1), excellent monodispersity, and homogeneous particle size. The introduction of ethanol into the reaction systems could expand the particle size of the synthesized MONs-SH materials from 18 to 182 nm. Moreover, the successful modification of -SH groups endowed MONs-SHs with an excellent adsorption capacity (297.12 mg g−1) for Pb2+ ions in aqueous solution through ion exchange and complexation function. In addition, the established isotherm model and kinetic analyses reveal that the adsorption of Pb2+ ions on MONs-SHs follows the secondary reaction kinetic models, where both physisorption and chemisorption contribute to the adsorption of Pb2+ ions. The favorable recyclability of MONs-SHs is demonstrated with the maintained adsorption efficiency of 85.35% after six cycles. The results suggest that the synthesized MONs-SHs exhibit considerable application prospects for effectively eliminating Pb2+ ions from aqueous solutions.